Jovens no ensino médio técnico: um olhar a partir das aulas de Matemática / Paula Resende Adelino - Paula Resende Adelino (2018)
This paper has as main objective to know a little more about the ways in which young people experience their school trajectory at the Technical School of Federal University of Minas Gerais (Coltec). To this end, we have considered, in the discursive interactions which took place in Mathematics classes of the second grade of Electronics of this institution during the academic year of 2015, positions assumed by these young people in their relation with the mathematical knowledge widespread in the school. We have chosen to focus the Mathematics classroom by its emblematic character, in a certain way, as a space in which the dynamics of the pedagogical relationships that happen at school are experienced and by the status of this subject in the school curriculum and, more specifically, in the curriculum of Electronics course, because it is a course of the area of exact sciences. We have taken the positions assumed by these students as a responsive attitude to legitimize their membership at this school, which is stressed by the speeches and other strategic procedures by which Coltec fulfills its educational purpose. In this research we have used reflections on territories and on the constitution of territorialities which were originally developed for the fields of Geography, Sociology and Economics, among others, but which have recently offered their analytical productivity to studies in the area of Education. Reflections on territories have allowed us to identify the Mathematics classroom and the school in general as spaces permeated by power relations, in which the subject performs functions and produces meanings, to exercise a certain domain over them and to develop a certain appropriation and, with this, to demarcate their belonging to these spaces. On the other hand, reflections on the constitution of territorialities would help us to understand the positions of the young people as tactical actions through which these Coltec students perform decisive functions to exercise the domain over that territory, to make feasible and to legitimize their permanence in it and to produce symbolic and practical effects of their experiences at this school and the narratives about them.